2020
DOI: 10.1155/2020/8867515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lubricant Additives on the Oxidation Characteristics of Diesel Engine Particulate Matter

Abstract: Three common lubricant additives, including an antioxidant, detergent, and an antifoamer, were added to diesel fuel to perform a diesel engine bench test. Particulate matter samples underwent thermogravimetric analysis to investigate the effect of lubricant additives on the particulate matter oxidation process, characteristic temperature, and activation energy. The results showed the following. Different lubricant additives result in different variation trends in the thermogravimetric curve of a particulate ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…e trend of decreasing log dynamic viscosity with respect to the log shear rate of the proposed oil having characteristics of non-Newtonian pseudoplastic fluid and correlation coefficient of the mathematical model is also close to unity. Xu et al [22] studied the influence of lubricating oil additives on the oxidation of particulate matter of diesel oil with thermogravimetric analysis and found that fuel of high cetane number reacts faster. Yao et al [23] evaluated that the high temperature is the prime reason for aero lubricating oil degradation.…”
Section: Introductionmentioning
confidence: 99%
“…e trend of decreasing log dynamic viscosity with respect to the log shear rate of the proposed oil having characteristics of non-Newtonian pseudoplastic fluid and correlation coefficient of the mathematical model is also close to unity. Xu et al [22] studied the influence of lubricating oil additives on the oxidation of particulate matter of diesel oil with thermogravimetric analysis and found that fuel of high cetane number reacts faster. Yao et al [23] evaluated that the high temperature is the prime reason for aero lubricating oil degradation.…”
Section: Introductionmentioning
confidence: 99%